Pengaruh Literasi Digital Terhadap Kinerja Usaha Tani Anggur di Kecamatan Tatanga Kota Palu - Alce Prischilia Molidja; Effendy Surentu; Rustam Abd. Rauf (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to analyze the influence of digital literacy on the performance of grape farming businesses in Tatanga District, Palu City. A quantitative explanatory approach with a cross-sectional survey was employed. A purposive sample of 63 grape farmers was used. Data were analyzed using Partial Least Squares-based Structural Equation Modeling (PLS-SEM). The results showed that digital literacy significantly influenced the performance of grape farming businesses, with an R² value of 0.678. Of the three dimensions of digital literacy, operational skills (β=0.630, p=0.000) and communication skills (β=0.384, p=0.038) had significant effects, while informational skills were not significant. These findings indicate that the practical ability to operate digital devices and communicate digitally has a more direct impact on business performance than merely searching for information. The study suggests that training programs focusing on operational and digital communication aspects are essential to improve the performance of grape farming businesses.